An on-going study of three different cervical cancer screening strategies based on primary healthcare facilities in Beijing China. Issue 4 (April 2020) - Han, Lili; Chang, Xinlei; Song, Peige; Gao, Lili; Zhang, Yue; An, Lin; Shen, Jie
Abstract: Background: To evaluate and compare the results of three different cervical cancer screening strategies including cytology screening, HR-HPV screening which taking HR-HPV testing as primary test and co-testing which taking both tests at the same time, then provide evidence to explore whether the cervical cancer screening can be conducted in community healthcare centers in Beijing. Methods: 182, 119 women aged between 35 and 64, who were screened in the primary healthcare facilities of nine districts in Beijing from January 2014 to March 2015, were enrolled in this study. Cytology screening was performed in participants during January 2014 and December 2014 as a conventional arm. HR-HPV screening strategy and co-testing were randomly allocated to participants on districts level as experimental arm 1 and 2 during January 2015 and March 2015. Cervical Intraepithelial Neoplasia grade 2 or worse (CIN 2+) was defined as endpoint. The screening results and costs to detect a case of three strategies were calculated. Results: The positivity rate, colposcopy referral rate and biopsy referral rate of co-testing were 8.46%, 6.36% and 4.65% respectively, which were all significantly higher than the other two screening strategies. The detection rate of CIN 2+ by co-testing was 5.06‰ and was much more than the other two screening strategies, while the HR-HPV screening had the highest PPV of 14.40%. The HR-HPV screening ignores some lesion which can be found by co-testing. Co-testing refers a woman to colposcopy with a positive screening result at the least cost, but it costs the most to detect a CIN 2+ case. Conclusions: To detect more cases of CIN 2+, co-testing performs better although with the most cost. And the primary healthcare facilities in Beijing have the capability to carry out the cervical cancer screen programs and prompts women with positive screen results to the hospital.